Trend Antimicrobial Resistance Patterns in Patients with Septic at The Intensive Care Unit : A Five years Retrospective Study - Nurkhalika, Rachmi; Sari, Ika Puspita; Nuryastuti, Titik (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Sepsis is a potentially fatal medical condition characterized by decreased organ function, lower mortality, and increased resistance. Antibiotic resistance can develop as a result of overuse and inappropriate indications. The WHO AWaRe classification categorizes antibiotics based on their potency and potential impact on antimicrobial multidrug resistance (AMR). This classification will make it easier to organize and select antibiotics, as well as reduce the occurrence of resistance. The goal of this study was to identify the pattern of bacterial resistance to antibiotics in septic patients from 2017-2021, as categorized by the WHO AWaRe classification. This study used a descriptive, non-experimental design and was carried out at the UGM Academic Hospital. The information was collected retrospectively from the medical records of patients diagnosed with sepsis in the intensive care unit and treated between January 2017-December 2021, who fulfilled the inclusion and exclusion criteria. According to the resistance pattern between 2017-2021, the gram-negative bacteria that caused sepsis were 55 isolates. The most common bacteria causing sepsis were Pseudomonas aeruginosa and Acinetobacter baumannii. When compared to antibiotics in the reserve category (meropenem and vancomycin), antibiotics in the access category (penicillin and/or beta-lactam inhibitors and first-generation cephalosporins), experienced the most resistance.